2017
DOI: 10.3389/fphar.2017.00767
|View full text |Cite
|
Sign up to set email alerts
|

Zolpidem Administration and Risk of Hepatocellular Carcinoma: A Case-Control Study in Taiwan

Abstract: Background/Objectives: Previous studies showed that zolpidem use could be associated with increased cancer risk, but the role of zolpidem on hepatocellular carcinoma (HCC) risk remains undetermined. The study purpose was to examine the association between HCC risk and zolpidem use in Taiwan.Methods: Using the database from the Taiwan National Health Insurance Program, we designed a case-control study which consisted of 77986 subjects aged 20 years or older with newly diagnosed HCC as the case group, and 77986 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…One population-based case-control study from Taiwan failed to detect a significant association between PPI use and the risk of developing HCC after adjusting for multiple confounders and excluding cases in which PPIs were administered within 1 year of HCC diagnosis. (33) However, that study included only a small proportion of patients with HBV (6.9%) or HCV (5.8%) and involved fewer patients than did the current study. In contrast, another recent study that included a large, well-defined cohort of HCV-infected veterans without cirrhosis in the United States revealed an association between PPI use and the risk of progression to liver cirrhosis, hepatic decompensation, and HCC.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…One population-based case-control study from Taiwan failed to detect a significant association between PPI use and the risk of developing HCC after adjusting for multiple confounders and excluding cases in which PPIs were administered within 1 year of HCC diagnosis. (33) However, that study included only a small proportion of patients with HBV (6.9%) or HCV (5.8%) and involved fewer patients than did the current study. In contrast, another recent study that included a large, well-defined cohort of HCV-infected veterans without cirrhosis in the United States revealed an association between PPI use and the risk of progression to liver cirrhosis, hepatic decompensation, and HCC.…”
Section: Discussionmentioning
confidence: 87%
“…(15) Nevertheless, the association between PPI use and HCC risk in patients chronically infected with hepatitis B virus (HBV) has been less clear. (33) Therefore, to help elucidate the association between PPI use and the risk of developing HCC among aRtICle INFoRMatIoN: patients with chronic HBV or HCV infections, we performed a population-based cohort study throughout Taiwan using the Longitudinal Health Insurance Database (LHID).…”
mentioning
confidence: 99%
“…Studies have suggested that nonviral hepatocellular carcinoma (HCC) is becoming a significant subgroup of HCC in East Asia. 1,2 This region has been endemic for chronic hepatitis C (HCV) and chronic hepatitis B (HBC), which resulted in a high incidence of viral-associated HCC. In Taiwan, it was estimated that approximately 20% of HCC cases are nonviral induced and 80% of them are related to chronic viral hepatitis.…”
Section: Editorsmentioning
confidence: 99%
“…In Taiwan, it was estimated that approximately 20% of HCC cases are nonviral induced and 80% of them are related to chronic viral hepatitis. [2][3][4][5][6][7] The proportion of nonviral induced HCC is still increasing because the prevalence of viral HCC is decreasing due to the success of universal vaccination 8 and anti-viral therapy. 9…”
Section: Editorsmentioning
confidence: 99%
“…All comorbidities were diagnosed based on ICD-9 codes. The accuracy of ICD-9 codes has been discussed in previous studies [33][34][35][36][37][38][39][40][41][42][43].…”
Section: Potential Comorbiditiesmentioning
confidence: 99%